The Soft Skills Inventory: Developmental procedures and psychometric analysis. Issue 1 (February 2022) - Jardim, Jacinto; Pereira, Anabela; Vagos, Paula; Direito, Inês; Galinha, Sónia
When attending and participating in Higher Education, students face a multitude of personal, social, and work-related challenges, which may increase the risk of developing psychopathological symptomatology. To date, there is no instrument that grasps the non-technical skills that may help prepare students to respond to these challenges. This paper presents the development and psychometric properties of the Soft Skills Inventory (SSI). The inventory was developed based on theoretical and empirical findings on the skills associated with academic and professional success, and on students' perception. The SSI was tested with 2030 Portuguese students (of which 77.1% were female) using a two-stage approach: item calibration and model generation (n = 1033), followed by model validation (n = 997). Item calibration analyses led to retaining 49 items that were organized into six-factors: self-determination, resilience, empathy, assertiveness, social support, and teamwork . This measurement model was further validated and proved to be an invariant, and thus credible, tool to compare male and female students on those relevant skills. All measures attained good internal consistency, with alphas ranging from .76 to .88. Female students scored significantly higher than males on self-determination, empathy, social support and teamwork. On the other hand, male students scored significantly higher on resilience. No significant differences were found between men and women for assertiveness. Psychometric analysis showed that the SSI is a reliable and valid instrument to evaluate students intra and interpersonal skills. The SSI may help identify gaps in soft skills and guide targeted interventions to support a more positive student experience in Higher Education.